OPTIMIZATION OF TRANSPORT AND LOGISTICS PROCESSES OF INDUSTRIAL ENTERPRISE - Khalipova, N. V.; Lesnikova, I. Yu.; Israfilova, N. A. (Systems and Technologies, 2018)
Analysis of transport-logistical processes of the enterprise at the present stage showed uneven condition and certain disproportions in their development. Was discovered that the problem is complex and one of the important drawbacks is the inefficient allocation and use of the existing transportation f leet. It is established that for the development of an industrial enterprise an important aspect is the organization of efficient transport and logistics processes, the planning of which should use the general principles, such as full satisfaction of enterprise structural units transport needs, efficient use of technical means and different types of resources, consideration of work of all types of transport in complex. he analysis shows that when planning the work of transport, the most difficult area is operational planning, whose functions are to establish agreed volumes of transport work and their units in the near future, routing of transportation, organization and coordinated work of transport and structural units of the enterprise. Continuous production at the enterprise requires constant prompt updating of existing solutions for transport and logistics support and warehouse solutions. To solve the problem of given production situation, it is proposed to use a multi-stage algorithm, which includes a sequential tasks solution: linear programming with limitations on the resources of the enterprise; the transport task and the task of the shortest distance from suppliers to warehouses for transportation of specified volumes of raw materials with the least cost; further formulation of conclusions and recommendations regarding the solution improvement and making the final decision. Microsoft Excel „Solution Finder‟ plugin was used to solve our optimization tasks. On the example of PrJSC Metinvest holding, an analysis of the existing transport and logistics support was carried out and the optimal raw material supply schemes were determined to ensure the operation of the resin-processing manufactory department. For continuous operation of the resin-processing department, it is necessary to have appropriate capacities for raw materials storaging. Based on the analysis of optimal raw material delivery schemes to support manufactoring, storage tanks capacity and the optimal delivery schedules for coal tar have been identified. The results of the study indicate the need for continuous prompt updating of existing solutions and can be used to improve the transport and logistics component of industrial enterprise processes.